Determinan Nilai Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021 - Sholeh Nur Rohmat; Axel Giovanni; Dian Marlina Verawati (Universitas 17 Agustus 1945, 2023)
Company Value is one of the company's goals to be achieved by maximizing the value of Shares. Company value is also one of the factors considered by investors when investing in the capital market. The company value of the food and beverage sub-sector for the last 5 years since 2017 has decreased significantly in 2019 to 2021. Firm Value is influenced by various factors such as: Managerial Ownership, Institutional Ownership, Profitability and Leverage. The existence of a research gap supported by the gap phenomenon makes further study of the factors that affect firm value still needed. This study aims to provide empirical evidence regarding the influence of Managerial Ownership, Institutional Ownership, Profitability and Leverage in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. The research population is all food and beverages on the Indonesia Stock Exchange (IDX). The research sample obtained as many as 57 observations through a purposive sampling method. Research using secondary data with analysis techniques using multiple linear regression analysis. The software tool used in the research is SPSS. The results of the study provide evidence of the influence of Managerial Ownership, Institutional Ownership and Leverage on Firm Value. However, there is also empirical evidence that Profitability has no effect on Firm Value. Meanwhile, simultaneously the variables of Managerial Ownership, Institutional Ownership, Profitability and Leverage affect Firm Value.